CHALLENGES IN CARE OF CHILDREN IN CORRUPTION CASES: ECONOMIC, SOCIAL AND CULTURAL ASPECTS - Junida, Dwi Surti; Mutmainnah, Inayatul (PT. Altin Riset Publishing, 2024)
Studies regarding the care of prisoners' children always involve the psychological problems that arise. So far, the existing findings do not examine the socio-economic perspective in the practice of caring for the children of prisoners. This research is important to do to find out how the family is able to organize itself. For support parenting children, what about stigma and discrimination to family prisoner influence methods they educate children their relationships with neighbors and community around impact on his upbringing and what his condition is like social economy influence parenting child prisoner? This research uses qualitative methods with in-depth interviews and participant observation, using case studies on families of corruption case inmates at Class 1 Correctional Institutions (Lapas) in Makassar City. Using an ethnographic approach with case studies through descriptive analysis of social structure, family structure, social support, and the impact of socio-economic conditions of prisoners on child care in terms of finances, education, employment, and economic support, which influence the ability of prisoner parents to provide adequate attention and care, worthy of their children. Researchers found that socioeconomic conditions play an important role in the upbringing of prisoners' children. Challenges in access to education and health services, economic limitations in providing care, and the impact of social stigma are important aspects that need to be considered in helping prisoners' families provide quality care for their children. By understanding the impact of these social and economic factors, it is hoped that this research can provide deeper insight and support in designing appropriate interventions to improve the quality of care for prisoners' children in families with limited socio-economic conditions.